Can a witness report hearsay evidence unintentionally? The effects of discussion on eyewitness memory - Kemp, Richard I (2011)
When eyewitnesses are exposed to misinformation about an event from a co-witness, they often incorporate this misinformation in their recall of the event. The current research aimed to investigate whether this memory conformity phenomenon is due to change in the witness's memory for the event, or to social pressures to conform to the co-witness's account. Participants were shown a crime video and then asked to discuss the video in groups, with some receiving misinformation about the event from their discussion partners. After a one week delay some participants were warned about possible misinformation before all participants provided their own account of the event. In Study 1, participants made remember/know judgments about the items recalled, and in Study 2 they indicated the source of their memories. Co-witness information was incorporated into participants' testimonies, and this effect was not reduced by warnings or source monitoring instructions, suggesting memory change may have occurred. However, there was some indication that remember/know judgments may help distinguish between "real" memories and co-witness information